PENGARUH LIQUIDITY, LEVERAGE, PROFITABILITY, FIRM SIZE DAN SALES GROWTH TERHADAP RISIKO SAHAM (Perusahaan Manufaktur yang Listing di BEI Tahun 2010-2013) - Sidauruk, Lhadualiese; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2015)
Invesment both individuals and businesses to invest spend money to get money more. Return value in invesment can be seen from the financial performance of the money invested. Risk can be considered as a possibility of loss or destruction. More broadly,the risk can be defined as the possibility of undesirable result or the opposite of the desired. In the financial industry in general, there is a jargon â€œbring about a high risk high returnâ€ meaning if want to obtain greater result, will be exposed to greater risk as well.The population of the study is a data manufacturing firm listed on Indonesian Stock Exchange in 2010-2013. The sample in this study amounted 58 companies by using purposive sampling. This study uses regression classical assumptions, to determine the variables that affect the risk of stockThe result of this study showed that there are three variables that affect significantly as stock risk. Variable leverage, profitability, sales growth have positive affect on stock risk, and liquidity and firm size did not influence and negative on stock risk.